The role of Shopping Tourism in the Restart of Tourism After the COVID-19 Crisis - AbuElEnain, EmadEddin Ahmed (Al-Adab Journal, 2021)
Shopping tourism is one of the most important tourism types that has an economic significance for tourism development in many tourist countries. Shopping has become a facilitator with a great influence in terms of the added tourism value of the tourist destination. Shopping has evolved to become an influential factor in determining the choice of a tourist destination, and sometimes the main tourist incentive to choose a specific destination. Tourism destinations have acquired great marketing opportunities as a result of this impression on the trends of innovative tourism markets through increased emphasis on unique shopping methods.In addition, this study is concerned with stimulating the development of this tourism pattern as an alternative in times of crises and making it one of the main tourist attractions. The research explores the elements and motives that motivate the improvement of this type and the developments that this field has witnessed in several international and Arab destinations. The study also explores ways to improve this type to become an independent tourist trend and its impact on changing the mental image of the tourism experience in tourist destinations and increasing the number of tourists, tourism nights and tourism revenues and their average expenditures, especially in times of crisis such as Covid 19 pandemic. The research also provides recommendations on measures that can encourage more tourists to visit shopping destinations around the world, especially in times of crisis.